Religion in the Kitchen : Cooking, Talking, and the Making of Black Atlantic Traditions - Perez, Elizabeth, 1975- (Book collections on Project MUSE., 2016)
Before honey can be offered to the Afro-Cuban deity Ochún, it must be tasted, to prove to her that it is good. In African-inspired religions throughout the Caribbean, Latin America, and the United States, such gestures instill the attitudes that turn participants into practitioners. Acquiring deep knowledge of the diets of the gods and ancestors constructs adherents' identities; to learn to fix the gods' favourite dishes is to be 'seasoned' into their service. In this innovative work, Elizabeth Perez reveals how seemingly trivial 'micropractices' such as the preparation of sacred foods, are complex rituals in their own right.